Application of TDABC in assessing the profitability of examinations and the level of idleness of computed tomography in the gynecological oncology sector - Pereira, Helcio Mendonça (2024)
Gynecological malignancies represent one of the main mortality factors in women, with imaging exams being important tools for diagnosis, staging and surgical planning. Such exams are carried out at Diagnostic Imaging Centers (CDI) which, due to the use of sophisticated technology and qualified labor, are expensive and impact health systems. Given this context, this research aims to demonstrate how TDABC can be used to evaluate the profitability of exams and the levels of idleness that exist in the context of the computed tomography sector of the gynecological oncology unit. For this purpose, a methodology classifiable as qualitative and descriptive was used and the case study format was adopted, with data collection through documentary research, informal interviews to learn about the process and estimates of the execution time of the activities. The results showed that the tests carried out are deficient, as the cost of providing these services is higher than the prices paid by the Unified Health System (SUS), which resulted in a total loss of R$ -79,347.04 in the month. The levels of idleness of the activities involved were also determined, both in terms of inactive minutes and in monetary values. Therefore, it was concluded that the total idleness of the tomography sector surveyed reached R$ 102,932.81 and is equivalent to 41.62% on average for the activities covered (varying between 3.66% in the case of equipment and 81.59% in relation to nurses’ activity).  Regarding the contributions made, it is worth noting that the information made available by TDABC can support actions aimed at reducing time between activities and optimizing the performance of the employees involved, in addition to demonstrating TDABC's adherence within the scope of entities that perform diagnostic imaging services. From the results obtained, it is concluded that it is essential to optimize processes to reduce exam time and increase productivity, as well as the need to readjust the values in the SUS table to avoid compromising investment of resources in other sectors of the hospital.